Strategi pengembangan bisnis Tour dan Travel pada PT. Tiwikrama Tour Indonesia - Moeryawan, Aldira Abroury; Wijaya, Fanji (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Tiwikrama Tour Indonesia is a company that deals with tour and travel transportation. PT. Tiwikrama Tour Indonesia has the following strengths: 1. Strategic location in the city center with good accessibility; 2. Consumer trust in car, tour, and travel services and weaknesses 1. Limited physical facilities and human resources (HR) that limit service capacity; 2. Lack of effective promotion and marketing to increase company visibility. 3. Operational opening hours, 3. Price cuts, 4. Unclear information media and Opportunities: 1. Utilizing technological advances as a tool for marketing and consumer rentals; 2. Increasing tourism sector in the city of Bandung, 3. Addition of vehicle units in demand from consumers, 4. Gaining trust from customers and threats that arise: 1. The emergence of many competitors, such as Tour and Travel, 2. More attractive offers related to promos and discounts by other companies exist, 3. Increasing rental prices. By using the Business Model Canvas method PT. Tiwikrama Tour Indonesia is expected to improve its business strategy to be more innovative and flexible to continue to follow trends and expand the market. Therefore, it is likely that this research will significantly contribute to PT's growth. Tiwikrama Tour Indonesia. The strategic steps that must be taken immediately are 1. providing the types of vehicles often rented by consumers, 2. Carrying out regular service or checks to provide security and comfort for consumers, 3. Social-Media such as Instagram, TikTok, and other websites are used as marketing media. 4. Designing applications to make it easier for consumers to rent.